2021
DOI: 10.3390/w13091190
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pathogens in Onsite Wastewater Treatment Systems: A Review of Design Considerations and Influencing Factors

Abstract: Conventional onsite wastewater treatment systems (OWTSs) could potentially contribute to the transmission of infectious diseases caused by waterborne pathogenic microorganisms and become an important human health concern, especially in the areas where OWTSs are used as the major wastewater treatment units. Although previous studies suggested the OWTSs could reduce chemical pollutants as well as effectively reducing microbial contaminants from onsite wastewater, the microbiological quality of effluents and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 231 publications
(425 reference statements)
2
27
0
2
Order By: Relevance
“…Protozoan grazing also affects the interactions between bacteria and other microorganisms in the soil [35,39]. Numerous studies have documented that predation mechanisms play a significant role in reducing the bacteria in water and wastewater filtration systems [23,33,47,[49][50][51][52]. This study showed that the presence of bacterivorous protozoa in the soil columns stimulated a more stable removal efficiency of fecal bacteria, than that in the absence of protozoa predation (Figure 3B).…”
Section: Effects Of Protozoa On E Coli Removal Efficiencies In the Soil Columnsmentioning
confidence: 64%
See 3 more Smart Citations
“…Protozoan grazing also affects the interactions between bacteria and other microorganisms in the soil [35,39]. Numerous studies have documented that predation mechanisms play a significant role in reducing the bacteria in water and wastewater filtration systems [23,33,47,[49][50][51][52]. This study showed that the presence of bacterivorous protozoa in the soil columns stimulated a more stable removal efficiency of fecal bacteria, than that in the absence of protozoa predation (Figure 3B).…”
Section: Effects Of Protozoa On E Coli Removal Efficiencies In the Soil Columnsmentioning
confidence: 64%
“…A report cited by Schlimme et al (1997), showed protozoa consumption rates of 9-266 bacteria per hour for a flagellate and 200-5000 per hour for a ciliate [54]. Bacterivorous protozoa were documented to have different feeding rates, depending on their species and prey density [49,54,65]. Although predation by protozoa was revealed as the mechanism of bacterial destruction [46,47,52], there is little information available to support the percentage of bacteria removal by protists in a filtration system.…”
Section: Effects Of Protozoa On E Coli Removal Efficiencies In the Soil Columnsmentioning
confidence: 99%
See 2 more Smart Citations
“…Helminths are also often considered as the primary constraint for the reuse of wastewater in agriculture because of their low infective dose and prolonged survival rate in the environment [ 18 , 19 , 20 ]. Developmental stages of endoparasites have been found in raw wastewater [ 20 ].…”
Section: Introductionmentioning
confidence: 99%